CIREBON GAMING ESPORT CLUB MANAGEMENT - Hidayat, Doni Nugraha; Sugiharto, Sugiharto; Soenyoto, Tommy (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
Electronic Sport abbreviated as Esport has a general meaning: an agility contest between individuals or groups that are not limited to physical activities and is carried out using tools that perform their functions electronically. This qualitative research aims to analyze the planning system (Planning), analyzing the organizing system (Organizing), analyzing the implementation system (actuating), analyzing the surveillance system (Controlling). This research uses a descriptive qualitative approach. The subjects in this study were administrators, coaches, and athletes at the Cirebon Gaming Esport club. This study uses data collection techniques with methods of observation (observation), interviews (interviews), and documentation. Data analysis techniques using data triangulation, namely data collection, data reduction, data presentation, and concluding. The results of this study are that the Cirebon Gaming Esport club has run proper organization management. In planning the Cirebon Gaming club, Esport plans activities for a period. In organizing the management together, carry out their respective duties and responsibilities. In the implementation of all members of the Cirebon Gaming Esport club together, help each other in carrying out activities that have been planned at the management meeting. At the supervision of the Cirebon Gaming Esport club conduct an evaluation after the activity is finished, the evaluation conducted will be reported at the end of the activity and sealed in the management.